2020
DOI: 10.1371/journal.ppat.1008840
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of IFN-γ and granulysin to the clearance of Plasmodium yoelii blood stage

Abstract: P. vivax-infected Retics (iRetics) express human leukocyte antigen class I (HLA-I), are recognized by CD8 + T cells and killed by granulysin (GNLY) and granzymes. However, how Plasmodium infection induces MHC-I expression on Retics is unknown. In addition, whether GNLY helps control Plasmodium infection in vivo has not been studied. Here, we examine these questions using rodent infection with the P. yoelii 17XNL strain, which has tropism for Retics. Infection with P. yoelii caused extramedullary erythropoiesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(83 reference statements)
0
9
1
Order By: Relevance
“…Of these, cytotoxic subcluster 4, which was enriched for CD8 T cells and defined by expression of several granzymes and perforin, likely represents cytotoxic effector T cells that target infected cells and is associated with low-burden granulomas. Our findings contrast with those in model systems like mice, which notably do not have the capacity to sterilize sites of infection and whose CD8 T cells also do not express granulysin ( Hojo-Souza et al., 2020 ). However, our findings are consistent with a recent study on lung tissue from Mtb-infected macaques which also found evidence of cytotoxic molecule expression associated with controlled infection ( Esaulova et al., 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Of these, cytotoxic subcluster 4, which was enriched for CD8 T cells and defined by expression of several granzymes and perforin, likely represents cytotoxic effector T cells that target infected cells and is associated with low-burden granulomas. Our findings contrast with those in model systems like mice, which notably do not have the capacity to sterilize sites of infection and whose CD8 T cells also do not express granulysin ( Hojo-Souza et al., 2020 ). However, our findings are consistent with a recent study on lung tissue from Mtb-infected macaques which also found evidence of cytotoxic molecule expression associated with controlled infection ( Esaulova et al., 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This problem is exacerbated by the potential acceleration of reticulocyte maturation after invasion, as seen in P. vivax ( Malleret et al., 2015 ). Additionally, studies with P. vivax and P. yoelii have shown that infected reticulocytes are more prone to removal by the host’s cytotoxic CD8+ T-cells ( Junqueira et al., 2018 ; Hojo-Souza et al., 2020 ), resulting in the underrepresentation of infected reticulocytes in circulation. Peripheral blood data are also made even more unreliable considering the extent of organ and deep vasculature sequestration of infected cells ( Franke-Fayard et al., 2010 ; Claser et al., 2011 ), and the presence of extravascular parasite populations in hematopoietic organs ( De Niz et al., 2018 ; Lee et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, however, another group using a more virulent strain of Py , Py NL , documented a key role for CD8 + T cells in the control of blood parasitemia, invoking both IFNγ- and Fas-L-dependent protection mediated by the CD8 + T cells and macrophages ( 34 , 35 ). The potential importance of CD8 + T cells during blood stage malaria, was also recently highlighted in Py (17XNL1.1) -infected transgenic mice expressing the human-restricted cytolytic effector molecule granulysin (GNLY) ( 36 ). Here, formal proof of concept that GNLY + CD8 + T cells, shown to recognize and kill P. vivax -infected MHC-I + reticulocytes (iRetics) ex vivo ( 37 ), could also kill MHC-I + Py- iRetics in this model ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential importance of CD8 + T cells during blood stage malaria, was also recently highlighted in Py (17XNL1.1) -infected transgenic mice expressing the human-restricted cytolytic effector molecule granulysin (GNLY) ( 36 ). Here, formal proof of concept that GNLY + CD8 + T cells, shown to recognize and kill P. vivax -infected MHC-I + reticulocytes (iRetics) ex vivo ( 37 ), could also kill MHC-I + Py- iRetics in this model ( 36 ). Other studies using the P. chabaudi murine model of infection that induces low chronic blood-parasitemia rebounds over 1-3 months post infection ( 13 , 38 ), have also reported CD8 + T cells, which express high cell-surface PD-1, to be essential in mediating effective blood stage parasite clearance during the chronic rebound phase and PD-1 blockade ( 13 ).…”
Section: Discussionmentioning
confidence: 99%